Ferramenta computacional para modelagem e validação automática de redes elétricas de distribuição de baixa tensão da BDGD para estudos estáticos e temporais em sistemas elétricos de potência - Rezende, Gabriel de Morais (Brasil, 2024)
Nowadays, low voltage distribution networks have been undergoing changes in energy consumption profiles and power flow direction due to the massive integration of distributed generation elements and electric mobility. These challenges have spurred the development of studies in the areas of protection, control, maintenance, and power quality. Most studies necessitate the use of the Distributor's Geographic Database (BDGD). This database, standardized by the Electric Energy Distribution Procedures in the National Electric System (PRODIST), contains the physical and eletrical characteristics of the elements of the electrical distribution network.However, the process of simulating these electrical networks involves transcribing data from the DGDB to the electrical models of simulation software widely used in academia and the electric power industry. Among them is OpenDSS, software that uses a textual language for modeling and simulating electrical networks at different voltage levels. This work proposes the creation of an environment that automates the modeling of electrical distribution networks for the OpenDSS software, using the BDGD as the basis. The automated environment will facilitate efficient and accurate data integration, processing, and conversion, thereby enhancing the analysis and planning of the electrical distribution system. In a Python program, a power grid is selected, and it's elements are filtered to generate scripts that model the components present in the chosen grid. After modeling the power grid, it is subjected to validation tests in another Python program. A total of 96 samples of low-voltage power grids are selected for these tests, which verify if the voltage and current levels for each sample are adequate, and if the simulated consumption aligns with the consumption values from BDGD. Finally, from the results of using the methodology, values of voltage levels at the nodes, currents in the loads, and monthly energy consumption of the simulated samples are obtained. Out of the 96 selected samples, 91 were tested, and 74 met the criteria defined in the methodology.